Burden of non‐motor symptoms in Parkinson's disease patients predicts improvement in quality of life during treatment with levodopa‐carbidopa intestinal gel. (26th December 2018) - Ray Chaudhuri, K.; Antonini, A.; Robieson, W. Z.; Sanchez‐Soliño, O.; Bergmann, L.; Poewe, W.; ,
Abstract : Background and purpose: GLORIA, a registry conducted with 375 advanced Parkinson's disease patients treated with levodopa‐carbidopa intestinal gel (LCIG) for 24 months in routine clinical care, demonstrated significant reductions from baseline in 'off' time and 'on' time with dyskinesia and improvements in the Non‐Motor Symptom Scale (NMSS) total and individual domain scores, and in Parkinson's Disease Questionnaire 8 item (PDQ‐8) total score. Methods: Associations between baseline NMSS burden (NMSB), the multi‐domain NMSS total score and the PDQ‐8 total score were investigated for 233 patients. Baseline NMSB was assigned to five numerical categories defined by the NMSS total cutoff scores (0–20, 21–40, 41–60, 61–80 and >80). Pearson and Spearman correlations were calculated at month 24. Results: The response of LCIG was assessed using validated criteria after 24 months. The proportion of patients decreasing ≥ 30 NMSS score points was 47% in the most affected NMSB category (NMSS total score > 80). A positive association was noted between baseline NMSB and NMSS total score (0.57, P  < 0.0001), as well as between NMSS total score and PDQ‐8 total score (0.46, P  < 0.0001). Associations between improvements of the NMSS domain sleep/fatigue and PDQ‐8 total score (0.32, P  = 0.0001) as well as between the NMSS domain mood/cognition and PDQ‐8 total score (0.37, P  < 0.0001) were also shown. Conclusions: This analysis demonstrated positive associations between NMSS baseline burden and improvements of non‐motor symptoms. Improvements of non‐motor symptoms were associated with improved quality of life in advanced parkinsonian patients during a 2‐year treatment with LCIG and reflect the long‐term non‐motor efficacy of this treatment.